Assessment of Response to Chemoradiation and Radiation Therapy in Patients with Nasopharyngeal Carcinoma - Susanto, Sebastian Ario; Dewi, Yussy Afriani; Saputri, Raden Ayu Hardianti (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Nasopharyngeal carcinoma (NPC) is a head-and-neck cancer that develops in the epithelial lining of the nasopharynx. The provision of radiotherapy and chemoradiation therapy in NPC can be evaluated by assessing the tumor response. AIM: The present study aims to determine the response in patients with nasopharyngeal carcinoma (NPC) to radiotherapy and chemoradiation therapy. METHODOLOGY: The study design is a retrospective bivariate analytic study from the Otorhinolaryngology-Head and Neck Society Head-Neck Surgical Oncology data registry program for the period of 2016−2021 at Dr. Hasan Sadikin General Hospital, Bandung. A total sample of 447 patients with NPC was used, and data were processed with descriptive and bivariate analytical tests. The variables used were patient characteristics and tumor response to radiotherapy and chemoradiation therapy. The tumor response was obtained based on the results of the examination at least 3 months after the administration of therapy and categorized according to the Response Evaluation Criteria in Solid Tumors 1.1 (RECIST 1.1). RESULTS: Three hundred and eighty-three NPC patients (252 men and 131 women) underwent chemoradiation or radiation therapy, and their tumor response had been evaluated. Most patients were diagnosed at Stages III and IV and treated by chemoradiation. In total, 314 of 383 patients (82%) achieved CR (complete response), 50 patients (13.1%) achieved PR (partial response), 11 patients (2.9%) had PD (progressive disease), and 8 (2.1%) patients had SD (stable disease). There is no statistically significant difference in the type of therapy response when correlated with the each of the variables; age, sex, and educational level (p > 0.05). There is a statistically significant difference in the type of therapy response among different clinical stage groups (p < 0.0001). CONCLUSION: Most nasopharyngeal carcinoma patients in the study had a complete response (82%) for either chemoradiation or radiotherapy alone. Age, sex, and education level have no significant effect on therapy response. On the other hand, the response to therapy is significantly correlated to the clinical stage of the disease.